Hebrajska nazwa "Yerûšalaim" w wybranych słowiańskich przekładach Ewangelii - Kawecka, Agata; Zarębski, Rafał (The Biblical Annals, 2024)
This article, which is part of a series of studies on biblical onyms, is devoted to the translation equivalents of the local name Yerušalaim (genetically Hebr.) in selected old Slavic translations of the Gospel, produced before the 17th century. The analysis of the material, carried out on the basis of the philological method, aims to show the equivalents of the toponym in the translations into particular languages, the degree of dependence in the rendering of this name between the translations and their sources, and to show the impact of some of the translations on others. The body of the texts constituting the instalments of the multilingual translation series of the Gospel consists of key and often better-known translations into the selected languages, representing the three main groups of Slavic languages (southern, eastern and western). The source material was selected so as to ensure diversity in the basis for translation (Greek vs. Latin), religious tradition and the translation strategy applied.